Diplomasi Publik Korea Selatan Terhadap Indonesia Melalui Media Sosial Tahun 2011-2014 - Ferdinand Melyanus Magal (Jurusan Ilmu Hubungan Internasional, 2015)
This article aims at analyzing South Korea’s efforts both government and non-government level in conducting public diplomacy towards Indonesia, using social media. Starting from 2011, the South Korean Embassy in Jakarta, routinely used Twitter and Facebook to give information about South Korea and its Jakarta Embassy’s activities. This article the effectiveness of social media based public diplomacy of South Korean embassy in Jakarta. This article highlights two important points: first, official information from government sector garnered more responses than from non-government sector. The second is that the Facebook is the ultimate medium to disseminate information of both government and non-government information from South Korean Embassy